Test of Total Volatile Base Nitrogen (TVB-N) in Tuna (Thunnus Sp.) at the at the Technical Implementation Unit for Quality Testing and Development of Marine and Fishery Product Banyuwangi, East Java - Agata Kinanthi; Eksi Dyah Yuliarti; Wahju Tjahjaningsih (Journal of Marine and Coastal Science, 2022)
Product quality is the physical condition, function, and nature of a product that can meet the tastes and needs of consumers, therefore there needs to be maximum efforts that can be made to maintain the quality of raw materials, especially fresh fish and the example is tuna fish. One of the parameters of fish chemical is total volatile base nitrogen (TVB-N). Testing the levels of TVB-N at the Technical Implementation Unit for Quality Testing and Development of Marine and Fishery Product Banyuwangi begins with sample characterization, including: complete weight, central temperature, pH and water content. The method used is guided by SNI 2354.8:2009 which consists of the preparation, distillation and titration stages. The standard level of TVB-N for fresh fish suitable for consumption according to SNI 2354.8:2009 is 20-30 mgN/100 g. The results of testing the levels of TVB-N of tuna fish samples ranged from 16.29-29.57 mgN/100 g, which means it is still within the acceptable level of consumption, that is suitable to SNI 2354.8:2009 is 20-30 mgN/100 g.